Fermentation quality and nutritive value of fresh and fermented total mixed rations containing Chinese wildrye or corn stover. (October 2016) - Cao, Yang; Zang, Yanqing; Jiang, Zaihui; Han, Yahui; Hou, JianJun; Liu, Huawei; Zhong, Rongzhen; Fang, Jiachen; Zhang, Aizhong; Yoshida, Norio
Abstract: Nutritive value of fresh or fermented total mixed ration (TMR) containing Chinese wildrye ( Leymus chinensis (Trin.) Tzval.) or dry corn ( Zea mays L.) stover was determined. The experimental treatments included fermentation and dietary roughage. The fermentation treatments included fresh and fermented TMR, while the dietary roughage treatments included Chinese wildrye and corn stover. Compared to the fresh TMR, the fermented TMR had higher ( P  <   0.05) contents of ether extract, lactic acid, acetic acid and ammonia‐nitrogen (N) but lower ( P  <   0.05) organic matter, non fibrous carbohydrate and neutral detergent fiber, and inhibited growth of molds in silages; moreover, the fermented TMR increased ( P  <   0.05) the digestibility of ether extract and neutral detergent fiber, and tended to increase ( P  <   0.05) the digestibility of acid detergent fiber, but also increased the concentration of ruminal total volatile fatty acid and valeric acid at 2 h of feeding, and ammonia‐N at 2 or 4 h of feeding. The silage with 10 mm corn stover had a higher ( P  <   0.05) lactic acid content, and reduced ( P  <   0.05) losses of non fibrous carbohydrate during fermentation compared with 50 mm treatment. Almost all chopped‐corn stover TMR had similar nutrient digestibility to Chinese wildrye. Among the eight TMRs, the fermented TMR with 10 mm corn stover had the highest intake ration of dry matter, while the fermented TMR with Chinese wildrye was the lowest. These results suggest that fermentation inhibit growth of molds in silage, decrease neutral detergent fiber, and then improve the nutrient digestibility. Chopped corn stover TMR had similar nutrient digestibility to Chinese wildrye TMR, and could replace Chinese wildrye in TMRs for ruminants.